Att komma från sitt lidande genom att skriva. Bränt barn söker sig till elden av Cordelia Edvardson som ett viktigt exempel på svensk vittneslitteratur - Ławniczak, Sonia (Folia Scandinavica Posnaniensia, 2024)
The purpose of the article is to show the way in which Cordelia Edvardson, the Swedish writer and eyewitness of the Holocaust, forms the work of recreating an identity beyond Auschwitz. Another purpose of this article is to show the way in which this book can promote and influence the creation of memorial images concerning the Second World War and Sweden’s participation in the global legacy of the Holocaust. In doing so, the analysis examines narrative instance and identifies textual strategies that promote the spread of a certain form of collective memory.